Literacy Learning in Early Grades: Teacher Thought on Teaching Literacy - Anggi Apriliana; Tatat Hartati; Dadang Sunendar; Rahman (Jurnal Ilmiah Sekolah Dasar, 2022)
The main problem in student's literacy skills in the early grades has not been implemented holistically. In addition, the teacher has not used the right model in literacy learning in the early grades. The main objective of this research was to analyses the process of learning literacy in elementary school. This study used a survey method involving 48 principals and 148 elementary school teachers. Interviews were used as an instrument to describe literacy learning in early grades of elementary schools. Information obtained from the field is tabulated and presented. This research showed that the procedures or models and learning media used by teachers are different. Teachers have made efforts to increase children's motivation in exploring literacy learning. Teachers believe that literacy is a very important need for every individual. Literacy in the early grades plays an important role in determining students learning success. Effective literacy learning in the early grades needs to pay attention to the learning environment and material that suit the needs of students. A pleasant learning experience and adult support can have a positive effect on reading skills. This skill will greatly affect subsequent literacy skills. If literacy learning in the initial class is not strong, it will be difficult for students to build a foundation for literacy in higher grades.